2023
DOI: 10.32473/edis-hs1466-2023
|View full text |Cite
|
Sign up to set email alerts
|

Using High Tunnels to Enhance Organic Vegetable Production in Florida: an Overview

Shufang Tian,
Xin Zhao,
Isaac R. Vincent
et al.

Abstract: Cost-effective high tunnel systems as a protected production tool hold great potential for offering multifaceted benefits to vegetable growers in Florida beyond season extension. The adoption of high tunnels in the U.S. has been largely fueled by the NRCS High Tunnel System Initiative. Various high tunnel structures may be adapted to the Florida environment for growing high-value vegetable crops. In particular, high tunnels can help improve crop yield and quality in organic vegetable production. This article p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Additionally, sandy soils that are typically low in organic matter content (<10 g/kg) make efficient water and nutrient management difficult (Li et al 2021a). With the increasing adoption of high tunnel systems among Florida vegetable producers (Tian et al 2023), more research-based information is needed to examine the impact of this cost-effective, protected culture system on crop yields and quality in sandy soils.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, sandy soils that are typically low in organic matter content (<10 g/kg) make efficient water and nutrient management difficult (Li et al 2021a). With the increasing adoption of high tunnel systems among Florida vegetable producers (Tian et al 2023), more research-based information is needed to examine the impact of this cost-effective, protected culture system on crop yields and quality in sandy soils.…”
mentioning
confidence: 99%
“…High tunnels are usually unheated, polyethylene-covered structures that use solar energy for heating and passive ventilation for cooling (Lamont 2009;Tian et al 2023). They are commonly employed to extend the growing season by providing a moderate level of environmental control (Frey et al 2020;Lamont 2009) and have been shown to improve crop yield and quality (O'Connell et al 2012).…”
mentioning
confidence: 99%